Impact of Early Childhood Care and Development Programme in Learning Mathematics - Kshetree, Mukunda Prakash (Tribhuvan University Journal, 2017)
The main focus of the study was to determine overall expected outcomes and learning achievements including assess the effectiveness of Early Childhood Care and Development (ECCD) models conducted in the support of Save the Children (SC) Nepal. The expected outcomes were related to children’s school preparedness, learning progresses, promotion, repetition and dropout status. The study was further focused on comparing achievement scores of the students (with and without ECCD exposure) in mathematics and other major subjects. The study also explored important areas for their corrective measures. The study adopted mixed methods research design which employed both quantitative and qualitative primary and secondary data. For the collection of required data, it administered different research tools including classroom observation, school survey forms and semi-structured interview schedules for teachers, parents, management committee members, community based organization (CBO) members and SC local staffs of three districts. The research tools were piloted in four schools located in Kavre district. The sample districts were selected purposively to involve each eco-zone of Nepal such as Siraha, Baglung and Achham from plain, hilly and mountainous region respectively. The study showed that the SC supported ECCD Centers were found above than average standard subjected to set out criteria. Similarly, the learning outcomes and achievements made by the students in major subjects including mathematics with ECCD experience showed significantly higher than those students having no ECCD experience.